Inhibition of histone deacetylase activity in human endometrial stromal cells promotes extracellular matrix remodelling and limits embryo invasion. - Carlos Estella; Isabel Herrer; Stuart P Atkinson; Alicia Quiñonero; Sebastián Martínez; Antonio Pellicer; Carlos Simón (PLoS ONE, 2012)
Invasion of the trophoblast into the maternal decidua is regulated by both the trophoectoderm and the endometrial stroma, and entails the action of tissue remodeling enzymes. Trophoblast invasion requires the action of metalloproteinases (MMPs) to degrade extracellular matrix (ECM) proteins and in turn, decidual cells express tissue inhibitors of MMPs (TIMPs). The balance between these promoting and restraining factors is a key event for the successful outcome of pregnancy. Gene expression is post-transcriptionally regulated by histone deacetylases (HDACs) that unpacks condensed chromatin activating gene expression. In this study we analyze the effect of histone acetylation on the expression of tissue remodeling enzymes and activity of human endometrial stromal cells (hESCs) related to trophoblast invasion control. Treatment of hESCs with the HDAC inhibitor trichostatin A (TSA) increased the expression of TIMP-1 and TIMP-3 while decreased MMP-2, MMP-9 and uPA and have an inhibitory effect on trophoblast invasion. Moreover, histone acetylation is detected at the promoters of TIMP-1 and TIMP-3 genes in TSA-treated. In addition, in an in vitro decidualized hESCs model, the increase of TIMP-1 and TIMP-3 expression is associated with histone acetylation at the promoters of these genes. Our results demonstrate that histone acetylation disrupt the balance of ECM modulators provoking a restrain of trophoblast invasion. These findings are important as an epigenetic mechanism that can be used to control trophoblast invasion.